Critical Factors and Institutional Role in Strengthening Capacity of National Parks: Analysis of Meru Betiri National Park, Indonesia Using Interpretative Structural Modeling - Merry Muspita Dyah Utami; Hari Rujito; Hendra Yufit Riskiawan; Didiek Hermanuadi (Jurnal Manajemen Hutan Tropika, 2020)
There are several factors suspected of ineffective rehabilitation and conservation of the Meru Betiri National Park. These important factors need to be identified to improve the management of the park. The purpose of this study was to identify and examine the relationship between the factors that influence the achievement of rehabilitation and conservation of the park. The method of this research used a systematic approach to be identified, analyzed, and explained the influential critical factors. Data and information collection was carried out through interviews with experts, management of Meru Betiri National Park, Jember Regency Government and then Focus Group Discussions with stakeholders and farmers. The information and data obtained were analyzed using Interpretative Structural Modeling (ISM). The results showed the three critical factors in achieving the purpose of the programs, such as the synergy between the management of the park and Jember district government; availability of appropriate technology; and the development of institutional capacity for local communities, then the three critical factors of institutional role are Meru Betiri National Park; and Development Planning Agency of Jember Regency; and Higher Education. The implication of this study is a policy intervention is needed to improve the management of Meru Betiri National Park in the future.